A pilot clinical trial to objectively assess the efficacy of electroacupuncture on gait in patients with parkinson's disease using body worn sensors - Lei, Hong; Schwenk, Michael (PLOS ONE, 2016)
BACKGROUND: Gait disorder, a key contributor to fall and poor quality of life, represents a major therapeutic challenge in Parkinson's disease (PD). The efficacy of acupuncture for PD remains unclear, largely due to methodological flaws and lack of studies using objective outcome measures.